THE IMPACT OF PRECEPTOR CARING AND PRECEPTORSHIP METHOD IN INCREASING THE CONFIDENCE OF THE NEW NURSE AT UKI GENERAL HOSPITAL JAKARTA [DAMPAK CARING PRECEPTOR DAN METODE PRECEPTORSHIP DALAM MENINGKATKAN PERCAYA DIRI PERAWAT BARU DI RSU UKI JAKARTA] - Erita Erita; Donny Mahendra (Universitas Pelita Harapan, 2019)
In his research Sung-Hyun Cho et al (2012) reported his research results that 27% of newly graduated nurses would leave their jobs within the first year if not well supported. Based on data of nurse personnel at UKI General Hospital in December 2016, the number of nurses moved another hospital 14% (24 people). New nurses entering the new workplace will face a variety of problems, the first month is a challenging time, stress, fear, lack of confidence and special difficulties in adapting to the work environment is common to newly groomed nurses and calling this fear a transition shock. The study aims to explore and interpret the experience of new nurses to caring preceptor in improving confidence after getting perceptorship assistance. Qualitative research method with phenomenology approach, sample number of 6 participants with purposive sampling technique at RSU UKI Jakarta in June to July 2017. Researcher's research instrument and interview guideline. Data analysis with NVivo 11 Plus has resulted in confident themes of new nurses with confident sub sub themes before and after preceptor mentoring. The theme of interpersonal relationships between preceptor and perceptee with sub theme caring and not caring preceptor. Conclusion The caring interaction between perceptor and perceptee can make the perceptee move toward self-actualization, self-esteem and self-esteem and progress that gives hope for the future, also makes perceptee feel better, happier, bolder and proud to work in that agency thus minimizing the turnover of new nurses. Researchers recommend the need for research on quality competence studies of preceptor. BAHASA INDONESIA ABSTRAK Dalam penelitian Sung-Hyun Cho et all (2012) melaporkan hasil penelitiannya bahwa 27 % dari perawat lulusan baru akan meninggalkan pekerjaannya dalam waktu satu tahun pertama bila tidak diberikan dukungan yang baik. Berdasarkan data tenaga perawat di Rumah Sakit Umum UKI bulan Desember 2016, jumlah perawat pindah rumah sakit lain 14 % (24 orang). Perawat baru ketika memasuki lingkungan kerja baru akan menghadapi berbagai masalah, bulan pertama merupakan masa yang penuh tantangan, stres, ketakutan, kurang percaya diri dan kesulitan khusus dalam beradaptasi dengan lingkungan kerja hal yang umum dialami perawat lulusan baru dan menyebut ketakutan ini sebagai transition shock. Penelitian bertujuan mengeksplorasi dan memaknai pengalaman perawat baru terhadap caring preceptor dalam meningkatkan percaya diri setelah mendapatkan pendampingan perceptorship. Metode penelitian kualitatif dengan pendekatan fenomenologi, jumlah sampel 6 partisipan dengan tehnik purposive sampling di RSU UKI Jakarta pada bulan Juni sampai Juli 2017. INstrumen penelitian peneliti dan pedoman wawancara. Analisis data dengan NVivo 11 Plus didapatkan hasil tema percaya diri perawat baru dengan sub tema percaya diri sebelum dan setelah pendampingan preceptor. Tema hubungan interpersonal antar preceptor dan perceptee dengan sub tema caring dan tidak caring preceptor. Kesimpulan Interaksi caring antara perceptor dan perceptee , dapat membuat perceptee mengalami pergerakan ke arah aktualisasi diri, peningkatan harga diri dan percaya diri serta mengalami kemajuan yang memberikan harapan untuk masa depan, juga membuat perceptee merasa lebih baik, bahagia, berani dan bangga bekerja di instansi tersebut sehingga meminimalkan turn over perawat baru. Peneliti merekomendasikan perlunya penelitian tentang kajian kualitas kompetensi preceptor.